Transmitters and Modulators in Health and Disease New Frontiers in Neuroscience - Shioda, Seiji; Homma, Ikuo; Kato, Nobumasa (Springer Japan : Imprint: Springer, 2009)
Prominent international researchers contributed to this volume of reports advancing the study of brain function and morphology. Comprising investigations in several areas of neuroscience, the book includes research in neurodegenerative diseases and in neuroregeneration in adults. Described here are the effects of neuropeptides and biogenic amines on feeding, respiration, and other autonomic functions as well as on behavior. One chapter focuses on regulation of the blood brain barrier function by various neuropeptides, proteins, receptors, and transporters. Another is concerned with the modulation of higher brain functions by neuropeptides and biogenic monoamines. Yet another chapter presents research on ischemic neuronal damage and hippocampal neurogenesis in the adult mouse. Morphological or physiological techniques to study neuropeptides and neuromodulators influencing higher-order or brain-stem functions are given particular attention. The use of bio-imaging tools such as brain navigation systems and fMRIs with patients in a clinical setting creates new possibilities for investigation of human brain function and specialization of treatment.